Formas de representações onomatopeicas em manuscritos escolares de histórias em quadrinhos produzidas por alunos do 2º ano do Ensino fundamental - Santos, Janayna Paula Lima de Souza (2010)
Resources verbal and nonverbal featuring the comic for children are considered actually factors which facilitate the entry of the child in writing and may contribute to the literacy process. Based on this assumption, discussed in this work, the functioning of linguistic and discourse of these features: the onomatopoeia. Thus, we take as its object “creation” of students from a 2nd year of elementary school and describe the different approaches aimed at her by some linguists, grammarians and lexicographers. Taking as its starting point this discussion, we analyze how these students represent onomatopoeia when they invent the text to a sequence of images of Mônica’s Gang comics. The manuscripts collected HQ schoolchildren are the products of 12 proposals for production of text made from the didactic project “Comics in the room”, developed in the 2nd half of 2008 in a public school in Maceió. The results show that the set of 144 manuscripts emerge onomatopoeia 291, classified by the sense invoked in four categories: 1) expressive onomatopoeia; 2) onomatopoeia action/motion; 3) indeterminate onomatopoeia; and, 4) onomatopoeia of animal sounds. Among them, point out five characteristics emerge with intensity: The first concerns the use of onomatopoeia of linguistic structure, namely, the reduplication of significant ways; the second refers to the relationship established between the image represented by comic and the onomatopoeia, this relationship is not always calm; the third related the similarities between the students productions and onomatopoeia in comics stabilized Mônica’s Gang; and the fourth is related to those forms “strange” that appear in some manuscripts; and the fifth feature points to the influence of orality in writing that represented some onomatopoeia provide large-print volume and intensity to it, as can be exemplified in the onomatopoeia “POFE” the title of this work. Along these lines, the research showed that onomatopoeia produced in the school situation maintain close relations with the graphic-visual aspects of their own gender and interrogate the concept of arbitrariness of the Saussurean sign proposed in the discussion. We hope with this study, the comic being a genus considered “suitable for work with written language” (BRAZIL, 2001, p. 111), contribute to the intensification of scientific research put into relief the processes of creation and writing of manuscripts school.